Penerapan Model Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Materi Penyajian Data Di Sekolah Dasar (International Forum of Researchers and Lecturers, 2024)
The problem of this research is that low mathematics learning outcomes are caused by students' low creative thinking abilities. This research aims to determine the increase in students' creative thinking abilities regarding data presentation at SDN Sukajaya through a problem based learning model, with a class V sample. The method used in this research is a quantitative experimental method with the type of Pre-Experimental Designs. The data collection technique uses observation, tests and documentation. The data analysis technique uses N-Gain. Based on the data analysis, the conclusion is obtained: there is an increase in the creative thinking abilities of fifth grade students at Sukajaya State Elementary School after using the problem based learning model in data presentation material, because seen from the results of the N-Gain test the value shows a value of 0.8, which is included in the high criteria. Calculations in this study used SPSS 26.